1H -NMR Metabolomics Study of the Effect of Cisplatin and Casiopeina IIgly on MDA-MB-231 Breast Tumor Cells - Resendiz-Acevedo, Karen; García-Aguilera, Martha E.; Esturau-Escofet, Nuria; Ruiz-Azuara, Lena (Frontiers in Molecular Biosciences, 2021)
The knowledge of the metabolic processes of designed metallodrugs for cancer treatment is an area that has been not profoundly studied. Casiopeina IIgly (CasIIgly), which belongs to the Casiopeínas® family, is a copper (II) coordination compound that has shown good biological activity against several cancer cells, low toxicity in normal cells, and antineoplastic activity in in vivo murine and xenografted models. In this work we employed a triple-negative highly metastatic breast carcinoma line (MDA-MB-231), which is one of the cancer types with a great mortality index, for 1H-NMR metabolomic analysis using cisplatin and CasIIgly, in order to quantify the effect of metallodrugs in the metabolic profile of this cell tumor line as a consequence of treatment at different times. Our findings indicate that cisplatin mainly contributes to phospholipid biosynthesis while CasIIgly affects processes such as carbohydrates and nucleotides metabolism. Also, we observed that CasIIgly treatment has an important and fast effect over MDA-MB-231 cell metabolism, which makes it a good alternative for treatment in this type of cancer.